Cross-Country Predictive Validities of Non-cognitive Variables for Mathematics Achievement : Evidence based on TIMSS 2015 - Lee, Jihyun; Chen, Minge (Eurasia Journal of Mathematics, Science and Technology Education, 2019)
This study presents empirical findings demonstrating predictive validities of non-cognitive variables for mathematics achievement among primary and secondary school students from cross-country perspectives. Results based on TIMSS 2015 assessment showed that confidence was a moderately strong predictor of mathematics achievement in all TIMSS participant countries (100%). Interest, on the other hand, was a moderately strong predictor in most countries for eighth-graders (77%) but only in about a dozen countries for fourth-graders (20%), showing a stronger interest-achievement link for the secondary school students, from the cross-national perspective. The sense of belonging measure demonstrated a lack of its relevance to primary school students' achievement. Further, bullying showed predictive relevance for student achievement only in three countries (South Africa, Jordan, and Egypt). The study concludes that while confidence was a universally relevant predictor of student achievement across all countries/regions, predictive utilities of interest, sense of belonging, and bullying appeared to be heavily dependent on a grade-level and country/regional context. [Author abstract]